A quasi-experimental study of specialized training on the clinical decision-making skills and social problem-solving abilities of nursing students. Issue 1 (4th March 2021) - Chen, Lin; Kong, Dong; Zhang, Shufang; Yang, Lijuan
Abstract : Background: In Asian countries, clinical practice places little emphasis on developing the clinical decision-making skills and social problem-solving abilities of nursing students. Objective: This study explored whether a 3-months-in-1-unit training program improved nursing students' clinical decision-making skills and social problem-solving abilities compared to the 1-month-in-1-unit rotation program. Methods: A quasi-experimental study was conducted. A 3-months-in-1-unit training program was conducted in the intervention group ( n  = 77), rountine1-month-in-1-unit rotation was conducted in the control group ( n  = 73). Clinical decision-making skills and problem-solving abilities were measured using the Chinese version of the Clinical Decision-Making Nursing Scale and the Social Problem-Solving Inventory–Revised. Results: Nursing students in the intervention group scored higher clinical decision-making skills ( t  = 7.677, p  < 0.05), positive problem orientation ( t  = 18.359, p  < 0.05), negative problem orientation ( t  = −3.711, p  < 0.05), and rational problem-solving ( t  = 2.312, p  < 0.05) than the control group. Conclusions: The 3-months-in-1-unit specialized training program had a significant positive impact on students' clinical decision-making skills and social problem-solving abilities.